Design and Dynamic Simulation of a Novel Lower Extremity Exoskeleton Robot for Power Assisting - Zeng, Yishan; Wang, Daoming; Zi, Bin; Wang, Shanjie (Recent Patents on Mechanical Engineering, 2016)
To increase the individual combat capability, a novel lower extremely exoskeleton robot (LEER) combining artificial intelligence and machinery is proposed for power assisting. The purpose of this study is to provide the design and dynamic simulation of a proposed novel LEER by addressing recent patents and scholarly articles. In this paper, recent developments and patents regarding the LEER are illustrated in detail firstly. Then, a structural design of the robot is performed which refers to the structure and motion freedom distribution of the human lower extremity joints to achieve a highly integrated of human-computer. Subsequently, the motion trajectory of main joints of the LEER is measured and the corresponding algorithm is fitted referring to the human normal walking gait. It is followed by a numerical simulation of the fitted algorithm using the Matlab software, and then the motion data of the corresponding joints is gained. Finally, dynamic simulation is conducted with the Adams software after importing the calculated motion data. And the motion data of the driving cylinder of each joint, including the displacement curve and driving force curve, are obtained. Simulation results indicate that the designed novel LEER can commendably simulate the human pace after the gait planning.
Keywords: Driving force